Comparison of Psychological and Physiological Stress in NICU Nurses: Effects of Unit Design and Shift. (August 2021) - Brand, M. Colleen; Shippey, Holly; Hagan, Joseph; Hanneman, Sandra K.; Levy, Barbara; Range, Stefany; Wongsuwan, Nattaya; Zodin, Amy; Walden, Marlene
Abstract : Background: Effects of unit design and shift worked on stress in neonatal intensive care unit (NICU) nurses have not been fully studied. Purpose: To compare stress in NICU nurses who work in single-family room (SFR) or open bay (OBY) units and on nonrotating day or night shift. Methods: Full-time registered nurses (RNs) (n = 72) from a 42-bed SFR and a 131-bed OBY NICU participated in this comparative cross-sectional study. The Nurse Stress Scale (NSS) and within-shift repeated salivary cortisol levels were used to measure stress. The relationship between NSS score and salivary cortisol level was examined using multiple linear regression. Salivary cortisol levels of day versus night shift were compared with mixed-effects linear models. Results: NSS scores were similar for SFR and OBY units ( P = .672) and day versus night shift ( P = .606). Changes in cortisol level over time ( P = .764) and final cortisol level ( P = .883) for SFR versus OBY were not significantly different after controlling for shift. Salivary cortisol level of day-shift nurses decreased significantly over time compared with night-shift nurses ( P < .001). The final cortisol level was significantly higher for night-shift compared with day-shift nurses ( P < .001). Implications for Practice: Psychological (NSS) and physiologic (salivary cortisol) stress of NICU nurses is similar in established SFR and OBY units. Cortisol levels are higher at the end of shift in nurses who work night shift and may reflect increased physiologic stress. Implications for Research: Strategies are needed for reducing stress in NICU nurses who work night shift.